جامع ترمذی کی کتاب التفسیر اور تفسیر سمرقندی کے تفسیری مشترکات ومُختَلَفَات: سورہ فاتحہ کا تحقیقی و تجزیاتی مطالعہ: Similarities and dissimilarities of tafsir book of Jami Tirmidhi and Tafsir Samarqandi: An explanatory and analytical study of Sura Fatiha - Muhammad Nawab Khan; Prof. Dr. Ata Ur Rahman; Dr. Maqsood ur Rehman (Al Manhal Research Journal, 2025)
Quran e karim is a noble book for the guidance of all humanity either they Muslims or Non-Muslims.it is the main source of knowledge beneficial for worldly life and for life hereafter. The explanation of Quran is called tafsir. As described in Surah Furqan “they bring to you no hypothesis, but we bring to youth correct position, and (answer) better explanation” The second source of knowledge is Hadis which defines and explains the holy Quran, the 3rd source of Holy Quran is the life of Sahabah (RA), the companions of Hazrat Muhammad ﷺwho were the first pupils and followers of Himﷺ. To get the explanation of the Holy book is called the science of Tafsir.Tafsir is defined by the Holy Quran itself like" واَنزَل اللہ ُ عَلَیک َالکِتَابَ وَالَحِکمَۃَ وَ عَلمَکَ مَا لَم تَکُن تَعَلَمَ"Allah has revealed to you the book and the wisdom ,and has a taught you what you did not know ” Now there are two types of mufassirin (the persons who explain the Holy Quraan) of the Holy Quran ,the first kind of mufassirin explain the Holy Quran, it may be authentic or non-authentic but the other type are the Muhaddisin (the specialists of Hadis) they always give an authentic explanation (tafsir).Among the prominent mufassirin one is Imam-e- Samarqandi (R.A), (301 or 311 A.H to 393 A.H) and among the prominent muhaddisin, Imam Tirmidi(R.A), (2009 A.H to 2079 A.H).so I selected the topic to explain and analyze the similarities and dissimilarities of both tafsir,s books. As our base of research is the book of Tirmidi so we take only those versus in which Imame Tarmidi has provided tafsir. The number of these Ahadis are415 .This will provide a difference of methodology of tafsir of muhaddis and mufassir and will also provide new angles in the science of tafsir.